Design Principles for Serious Video Games in Mathematics Education: From Theory to Practice - Konstantinos Chorianopoulos; Michail Giannakos (Serious Games Society, 2014)
There is growing interest in the employment of serious video games in science education, but there are no clear design principles. After surveying previous work in serious video game design, we highlighted the following design principles: 1) engage the students with narrative (hero, story), 2) employ familiar gameplay mechanics from popular video games, 3) engage students into constructive trial and error game-play and 4) situate collaborative learning. As illustrated examples we designed two math video games targeted to primary education students. The gameplay of the math video games embeds addition operations in a seamless way, which has been inspired by that of classic platform games. In this way, the students are adding numbers as part of popular gameplay mechanics and as a means to reach the video game objective, rather than as an end in itself. The employment of well-defined principles in the design of math video games should facilitate the evaluation of learning effectiveness by researchers. Moreover, educators can deploy alternative versions of the games in order to engage students with diverse learning styles. For example, some students might be motived and benefited by narrative, while others by collaboration, because it is unlikely that one type of serious video game might fit all learning styles. The proposed principles are not meant to be an exhaustive list, but a starting point for extending the list and applying them in other cases of serious video games beyond mathematics and learning.